2023
DOI: 10.3390/ijerph20053875
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medical Service Response Time for Road Traffic Accidents in the Kingdom of Saudi Arabia: Analysis of National Data (2016–2020)

Abstract: Despite preventive measures and initiatives, road traffic accidents are on the rise in the Kingdom of Saudi Arabia. This study aimed to investigate the emergency medical service unit’s response to RTA by socio-demographic and accident-related variables in the Kingdom of Saudi Arabia. This retrospective survey included Saudi Red Crescent Authority data on road traffic accidents between 2016 and 2020. As part of the study, information on sociodemographic characteristics (e.g., age, sex, and nationality), acciden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…This study found that the incidents of ambulance crashes were higher in the month of April followed by February and over the past three years, the month of April in the Gregorian Calendar was equivalent to the holy month of Ramadan in the Islamic Hijri Calendar which has been known for its high rates of RTAs [ 1 , 16 ]. The Holy Ramadan is a religious ritual with reduced working hours for employees and students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study found that the incidents of ambulance crashes were higher in the month of April followed by February and over the past three years, the month of April in the Gregorian Calendar was equivalent to the holy month of Ramadan in the Islamic Hijri Calendar which has been known for its high rates of RTAs [ 1 , 16 ]. The Holy Ramadan is a religious ritual with reduced working hours for employees and students.…”
Section: Discussionmentioning
confidence: 99%
“…The high population and urbanization of these cities and the higher frequency of traffic could account for the number of accidents, as they are consistent with studies from other countries [ 17 , 18 ]. A recent study from Saudi Arabia analyzed the national data of EMS response time for RTAs and reported the capital city of Riyadh marked the highest proportion of the RTAs followed by Makkah region [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Socio-demographic characteristics of participants: The socio-demographic information of participants from nine distinct studies is included in Table 1, which summarises the large number of cases from references [20][21][22][23][24][25][26][27][28]. These studies' geographic scope is constrained because they were all selected within Saudi Arabia's regions, like the Aseer region [22], Al Kharj [23], Riyadh [24,26], Tabuk [25], Eastern Province [27], and Ha'il [28].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…These studies' geographic scope is constrained because they were all selected within Saudi Arabia's regions, like the Aseer region [22], Al Kharj [23], Riyadh [24,26], Tabuk [25], Eastern Province [27], and Ha'il [28]. The research methodology of the reviewed studies [23,[25][26][27] used a cross-sectional design; one study [20] was Analysis of national data, and the others [21,22,24,28] were retrospective studies.…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…[ 2 ] Moreover, MVA was reported to be the most frequent cause of premature death in Saudi Arabia from 2007 to 2017, with a high occurrence of MVA reported in the city of Jeddah. [ 3 ] MVA-related deaths are a growing cause of public concern due to the physical, mental, and financial burden on individuals and families involved. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%